2014
DOI: 10.1007/s10802-014-9892-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teacher-Child Relationship Quality and Teacher-Rated Behavioral Adjustment Amongst Externalizing Preschoolers: Effects of a Two-Component Intervention

Abstract: The school-based Playing-2-gether is a 12-week intervention with two components aimed at decreasing child externalizing behavior through improving teacher-child interactions. The first component is rooted in attachment theory and aimed at enhancing teacher-child relationship quality, and the second is based on learning theory and aimed at improving teachers' behavior management. In this three-wave randomized study, effects of Playing-2-gether on the teacherchild relationship quality and on teacher-rated child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 51 publications
1
54
1
1
Order By: Relevance
“…Similarly, while a handful of prevention programs improving teacher–student relationships have been developed and successfully implemented in preschools (Driscoll and Pianta 2010; Vancraeyveldt et al 2015), none, to our knowledge, have been developed for teachers of adolescents. The lack of efforts in this area maybe due, at least in part, to lack of direct evidence for the causal effects of these relationships on student outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, while a handful of prevention programs improving teacher–student relationships have been developed and successfully implemented in preschools (Driscoll and Pianta 2010; Vancraeyveldt et al 2015), none, to our knowledge, have been developed for teachers of adolescents. The lack of efforts in this area maybe due, at least in part, to lack of direct evidence for the causal effects of these relationships on student outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is because for dyadic variables in multi-level contexts, such as classrooms governed by the interplay of a multitude of social-contextual and individual-dispositional factors, it is far from clear how results from experimental studies generalize to the real world. The few intervention studies that have been conducted found support for the idea that teacher–student relationships impact on behavioral outcomes (e.g., Driscoll and Pianta 2010; Vancraeyveldt et al 2015); however, they did not examine whether the change in behavior was a direct consequence of the achieved teacher–student relationship and were focussed on pre-schoolers; providing limited information about effects later in development.…”
Section: Introductionmentioning
confidence: 99%
“…Banking Time (Driscoll & Pianta, ), for instance, aims at improving teachers’ sensitivity and affective teacher–child relationship quality by organizing one‐on‐one child‐directed sessions. Building on this and other related interventions (e.g., McIntosh, Rizza, & Bliss, ), Playing‐2‐Gether (Vancraeyveldt et al., ) combines attachment theory and learning theory with the aim of improving both affective teacher–child relationship quality and teachers’ behavioral management. Although these interventions have targeted preschool children, the core attachment‐based principles (e.g., conveying acceptance and sensitivity) may also extend to middle childhood.…”
Section: Interventions To Improve Dyadic Teacher–child Relationship Qmentioning
confidence: 99%
“…This study aims to address these gaps by investigating the role of teacher–child interactions in academic engagement and achievement using an intervention study among preschool boys with signs of externalizing behaviour. Specifically, a randomized controlled trial study was set up with the preventive intervention Playing‐2‐gether (P2G; Vancraeyveldt, Van Craeyevelt, Verschueren, & Colpin, ; Vancraeyveldt et al ., ), an indicated intervention for externalizing preschoolers and their teachers, aimed at improving the affective quality of the teacher–child relationship and teacher behaviour management.…”
Section: Introductionmentioning
confidence: 99%
“…Vancraeyveldt et al . () found positive P2G effects on the affective quality of the teacher–child relationship, as well as on children's externalizing behaviour. Intervention effects on other child adjustment outcomes, such as academic outcomes, have not been studied up until now.…”
Section: Introductionmentioning
confidence: 99%